Promises and paradoxes of regulatory T cells in inflammatory bowel disease - Lord, James D (World J Gastroenterol, 2015)
Since their discovery two decades ago, CD4(+)CD25(+)Foxp3(+) regulatory T cells (Tregs) have become the subject of intense investigation by immunologists. Unlike other T cells, which promote an immune response, Tregs actively inhibit inflammation when activated by their cognate antigen, thus raising hope that these cells could be engineered into a highly targeted, antigen-specific, immunosuppressant therapy. Although Tregs represent less than 10% of circulating CD4(+)T cells, they have been shown to play an essential role in preventing or limiting inflammation in a variety of animal models and human diseases. In particular, spontaneous intestinal inflammation has been shown to occur in the absence of Tregs, suggesting that there may be a Treg defect central to the pathogenesis of human inflammatory bowel disease (IBD). However, over the past decade, multiple groups have reported no qualitative or quantitative deficits in Tregs from the intestines and blood of IBD patients to explain why these cells fail to regulate inflammation in Crohn’s disease and ulcerative colitis. In this review, we will discuss the history of Tregs, what is known about them in IBD, and what progress and obstacles have been seen with efforts to employ them for therapeutic benefit.